2016
DOI: 10.4254/wjh.v8.i11.520
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality after transjugular portosystemic shunt

Abstract: AIM:To investigate if echocardiographic and hemodynamic determinations obtained at the time of transjugular intrahepatic portosystemic shunt (TIPS) can provide prognostic information that will enhance risk Predictors of mortality after transjugular portosystemic shunt Retrospective Study ORIGINAL ARTICLEstratification of patients. METHODS:We reviewed medical records of 467 patients who underwent TIPS between July 2003 and December 2011 at our institution. We recorded information regarding patient demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
4
23
0
2
Order By: Relevance
“…The transjugular intrahepatic portosystemic shunt (TIPS) reduces portal pressure and relieves the clinical symptoms associated with various medical conditions[3]. TIPS has found a wide range of applications, including treatment of portal hypertension due to cirrhosis, variceal bleeding (VB), refractory ascites (RA), hepatic hydrothorax, hepatorenal syndrome, Budd–Chiari syndrome, hepatopulmonary syndrome, and portal thrombosis and as a bridge to liver transplantation[4].…”
Section: Introductionmentioning
confidence: 99%
“…The transjugular intrahepatic portosystemic shunt (TIPS) reduces portal pressure and relieves the clinical symptoms associated with various medical conditions[3]. TIPS has found a wide range of applications, including treatment of portal hypertension due to cirrhosis, variceal bleeding (VB), refractory ascites (RA), hepatic hydrothorax, hepatorenal syndrome, Budd–Chiari syndrome, hepatopulmonary syndrome, and portal thrombosis and as a bridge to liver transplantation[4].…”
Section: Introductionmentioning
confidence: 99%
“…Transjugular intrahepatic portosystemic shunt (TIPS) is currently used for the treatment of complications of portal hypertension[1]. The establishment of TIPS is widely accepted as an alternative to surgery in the management of complications from portal hypertension such as variceal bleeding, refractory ascites, Budd-Chiari syndrome, hepatorenal syndrome, hepatic hydrothorax, and even hepatopulmonary syndrome[2]. After TIPS was introduced as an alternative treatment for complications related to portal hypertension, it was progressively recognized as an effective therapeutic option in a growing number of clinical situations[3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the absence of diastolic dysfunction on echocardiogram essentially ruled out post-TIPS cardiac decompensation. Similarly, Ascha et al 36 assessed pre-and post-TIPS right atrial pressures and found pre-TIPS right atrial pressure of > 9 mm Hg to be a predictor of 3-month survival after TIPS. However, patients with higher right atrial pressures also had worse liver disease, and when adjusted for age, MELD score, and Child-Pugh class, the effects of right atrial pressure on survival became nonsignificant.…”
Section: Cardiac Diseasementioning
confidence: 98%